A Rare Case of Flatbush Diabetes: Clinical Manifestation and Diagnosis - Tutul Chowdhury (A Case in a Million, 2023)
This chapter discuss about a rare case of flatbush diabetes. Diabetes is broadly categorized as diabetes mellitus, diabetes insipidus, and gestational diabetes, with diabetes mellitus and diabetes insipidus having further subcategorizations of type 1 and type 2. Ketone-prone diabetes, commonly known as “Flatbush Diabetes”, refers to a hybrid form of diabetes that has various characteristics of type 1 diabetes and type 2 diabetes. It is typically seen in obese middle-aged men with a family history of Type 2 DM. We report about a 86-year-old woman with a past medical history of hypercholesterolemia, and hypertension controlled with 10 mg of Amlodipine, was admitted for confusion, polyuria, and polydipsia. Globally, there is a growing observation of atypicality in the start of age and gender variance. Extensive studies are necessary since one of the numerous uncertain pathophysiologic factors is the predisposition to glucose sensitivity. Due to the restored activity of pancreatic beta cells, many patients who receive rigorous insulin therapy eventually become insulin-independent and achieve euglycemia with oral hypoglycemic medications or diet alone. Our report sheds light on the atypicality of presentation and summarizes the main diagnostic features of this rare form of diabetes. It is of utmost importance to anyone dealing with diabetes to recognize this ubiquity especially with the rising prevalence of this disease.